Tratamento de efluentes de biodiesel pelo processo combinado de coagulação-floculação e fenton - Aline Morena Menezes Santos (2014)
Biodiesel is produced mainly by transesterification, a chemical reaction involving triglycerides, alcohol and catalyst. The effluent generated in this process is considered highly polluting and has free glycerol, soap, excess alcohol, residual catalyst and emulsified oil. The present study aims to characterize the effluent of the biodiesel purification process and evaluation of treatment alternatives using coagulation-flocculation methods and advanced oxidation by Fenton process. The samples were characterized by pH, turbidity, color, COD, BOD5, COD, oil and grease and biodegradability. The factorial design was employed in the coagulation-flocculation tests in which we selected The best of three coagulant (aluminum sulfate, ferric chloride and polyaluminum hydroxychloride) and experimental conditions (coagulant dose; effluent pH) suitable for treatment. Additionally, the Fenton process was optimized in terms of concentrations of [Fe2 +]:[H2O2] in a factorial design. Experimentally, it was observed that the collected effluents presented high organic loads and COD/BOD5 raties. Biodegradation tests conducted with pure effluent (Effluent D) showed poor biodegradability, however, the effluent dilution provides increased degradation. In the coagulation-flocculation tests coagulant polyaluminum hydroxychloride showed color removal efficiency (86%), turbidity (97%) and COD (30%) under the experimental conditions coagulant dose: 3,0 mg.L-1 , pH = 5, flocculant dose = 40 mg.L-1 . Three sets of experiments were performed using Fenton process and the ratio [Fe2 +]:[H2O2]= 2 resulted in better removal efficiency of COD (50%) under the conditions of [H2O2] = 1.500 mg.L-1 ) and [Fe2+]= 250 mg.L-1. The best experimental conditions of treatment by coagulation-flocculation and Fenton process were combined and resulted in COD removal efficiency of around 60%.